O12.1 Exploring relationship duration among gay and bisexual men: a longitudinal event-level analysis. (14th July 2019) - Card, Kiffer; Armstrong, Heather; Pan, Shenyi; Lachowsky, Nathan; Hogg, Robert; Roth, Eric; Moore, David
Abstract : Background: We characterized event-level relationship patterns of gay and bisexual men (gbMSM)'s long- and short-term with the goal of improving intimacy, well-being, and the control of sexually transmitted infections. Methods: Between 2012–2015, sexually-active gbMSM, aged > 16, were recruited in Metro Vancouver using respondent-driven sampling. Participants completed computer-assisted self-interviews at six-month intervals for up to 12 visits. At each visit, participants described their last sexual encounter with up to five of their most recent partners. Relationship duration was measured as the months between their first and most recent sexual encounter with each partner. Multivariable generalized estimating equations with RDS-chain, participant, and visit effects were used to identify sociodemographic, psychosocial, and behavioural factors associated with relationship duration. Results: A total of 10, 424 events were reported by 762 gbMSM (median=13/person, Q1 -Q3 :5–24). Median relationship duration was <1 month (Q1 -Q3 : 0–3) and the median number of sex events between partners was 1 (Q1 -Q3 : 1–1). Analyses indicate that longer relationship duration was associated with increasing age of participants (p<0.001); indigenous ethnicity (versus White; p=0.003); marijuana use before/during sex (p=0.014); and having met at a bathhouse (p=0.004), bar/club (p<0.001), through friends (p<0.001), or at another location (p=0.002; versus 'online'). Shorter relationship duration was associated with higher communal altruism (p=0.019); bisexual identity (versus gay; p=0.004); Latin American ethnicity (versus White; p=0.028); living with HIV (p=0.0004); not knowing the event-level partner's serostatus (p<0.001); engaging in insertive condom-protected anal sex with even-level partner (p=0.031); engaging in event-level group sex (p=0.001); and having sex at a park (p=0.004), hotel (p=0.043), private sex party (p=0.019), or other location (p=0.002; versus 'home'). Conclusion: Partner meeting location, personal identity, and risk management behaviours are key correlates of relationship duration – with shorter, often one-time, relationships being characterized by both risk (e.g., group sex, public sex, unknown partner serostatus) and risk management (e.g., condom use). Disclosure: No significant relationships.